DAYA HIDUP DAN INTENSITAS SERANGAN RAYAP KAYU KERING CRYPTOTERMES CYNOCEPHALUS LIGHT. PADA KAYU KELAPA (COCOS NUSIFERA L.) - Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
This study investigated termite survival and infestation intensity on coconut wood. For this purpose dry wood termite Cryptotermes cynocephalus Light. has been used in the experiment. Fifteen worker termites were placed in the wood coconut samples. The size of each sample is 1,5 cm by 2,5 cm by 5,0 cm. Samples were taken from the periphery and center of base of stem, the periphery and center of middle of stem and the periphery and center of top of stem .The result revealed that the highest dry wood termite survival accured at the central part of the top of stem (37,3%), where as the highest infestation intensity accured at the base of the stem.